Modeling of motor transport exhaust pollutant dispersion - Vaitiekūnas, Petras; Banaitytė, Reda (Journal of Environmental Engineering and Landscape Management, 2007)
Pollution is a major problem in all countries, even developed ones. It is the major environmental negative impact of anthropogenic activities affecting ecology. There are two major ways for assessment of negative impact of motor transport flow intensity and pollution level: monitoring the air or modeling pollutant dispersion. It is very important to estimate different unknown air modeling programs. In this work modeling is to be executed by the US EPA (United States Environmental Protection Agency) the so‐called “the best possible existing software for strategic environmental assessment”. That is also recommended by the Ministry of Environment of the Republic of Lithuania. In this work pollution modeling was executed for the northern part of Vilnius (the network of streets Geležinis Vilkas ‐ Ozas ‐ Kalvarijos). For motor vehicle pollution mathematical modeling, it is necessary to evaluate meteorological parameters like temperature, humidity, the wind direction and speed. Modeling software can also estimate relief conditions. Pollution emission measurements were used, and pollution dispersion modeling was performed. The main target was to evaluate pollutant dispersion from motor transport in the analysed area of Vilnius. During investigation maximum hourly, daily and annual concentrations of carbon monoxide, nitrogen oxide, sulphur dioxide, volatile organic compounds and particulate matter were observed.Automobilių išmetamų teršalų sklaidos modeliavimasSantrauka. Didžiuosiuose Lietuvos miestuose žymus transporto priemonių skaičiaus didėjimas. Transporto priemonių spūstys neišvengiamai verčia ieškoti būdų aplinkos oro užterštumui mažinti. Transporto priemonių išmetamų dujų neigiamą poveikį ir užterštumo lygį galima įvertinti dviem būdais – oro taršos stebėsenos arba teršalų sklaidos modeliavimo būdu. Automobilių išmetamų teršalų modeliavimas naudojant JAV priimtą ir US EPA (United States Environmental Protection Agency) patvirtintą bei LR aplinkos ministerijos rekomenduojamą teršalų sklaidos aplinkos ore matematinį modelį ISC3 atliktas Vilniaus miesto centrinėje dalyje (Ozo – Kalvarijų – Šiaurinės – Geležinio Vilko gatvių tinklas). Automobilių išmetamų teršalų skaitiniam modeliavimui atlikti būtina įvertinti meteorologines – atmosferos, reljefo, vėjo stiprumo ir krypties sąlygas. Remiantis turimais taršos emisijų duomenimis, atliktas jų sklaidos modeliavimas Gauso pasiskirstymo su empirinėmis pataisomis principu, nustatytos anglies monoksido, sieros ir azoto dioksido, lakiųjų organinių dalelių bei kietųjų dalelių maksimalios vienkartinės, paros, mėnesio ir metų vidutinės koncentracijos. Vienas iš darbo tikslų – įvertinti šios modeliavimo programos pritaikomumą Lietuvoje.Reikšminiai žodžiai: automobilių transportas, oro tarša, teršalai, sklaida, ISC-Aermod View modelis, koncentracija.Моделирование распространения выбрасываемых из автотранспорта загрязнителейРезюме. В больших городах Литвы значительно увеличилось количество автотранспорта. Скопление автотранспорта вынуждает искать способы уменьшения загрязненности воздуха. Отрицательное воздействие выбрасываемых из автотранспорта газов и аэрозолей и степень загрязненности можно оценить двумя способами – мониторингом загрязнения воздуха или моделированием распространения загрязнителей в воздухе. Моделирование выбросов из автотранспорта с использованием принятой в США и утвержденной US EPA (United States Environmental Protection Agency), а также рекомендованной Министерством окружающей среды Литовской Республики математической модели ISC3 выполнено в центральной части города Вильнюса (в сeти улиц Озо–Шяуринес–Гележинё Вилко). При моделировании необходимо учитывать метеорологические условия (атмосферные, силу и направление ветра), а также рельеф местности. С использованием имеющихся данных об эмиссиях загрязнителей выполнено моделирование их переноса в приземном слое по Гаусовому принципу распространения с рядом эмпирических поправок; установлены максимальные, одноразовые, суточные, месячные и среднегодовые концентрации окиси углерода, диоксида серы и азота, Летучих органических соединений и твердых частиц. Одной из целей работы было оценить пригодность этой программы моделирования в условиях Литвы.Ключевые слова: автотранспорт, загрязнение воздуха, загрязнители, модель „ISC-Aermod View“, концентрация.First Published Online: 14 Oct 2010